Survey Fatigue—Literature Search and Analysis of Implications for Student Affairs Policies and Practices - Fass-Holmes, Barry (Journal of Interdisciplinary Studies in Education, 2022)
Undergraduates’ low participation/response rates on interdisciplinary (campus-wide) and disciplinary (specific department) surveys have been attributed to survey fatigue. To investigate this attribution’s merits, the present study conducted a systematic literature search ( five electronic databases plus one search engine) and critiqued findings of relevant publications returned by the search. This study found that (a) survey fatigue has not been rigorously defined, (b) the number of relevant peer-reviewed publications is unexpectedly limited, and (c) their findings are contradictory. These results have implications for policies and practices that restrict undergraduate survey administrations to minimize survey fatigue and boost participation/response rates. The present report recommends improving undergraduates’ participation/response rates by requiring instruction about surveys combined with assessments of student learning outcomes.